2021
DOI: 10.1111/cpr.13104
|View full text |Cite
|
Sign up to set email alerts
|

RAB14 GTPase is essential for actin‐based asymmetric division during mouse oocyte maturation

Abstract: Objectives RAB14 is a member of small GTPase RAB family which localizes at the endoplasmic reticulum (ER), Golgi apparatus and endosomal compartments. RAB14 acts as molecular switches that shift between a GDP‐bound inactive state and a GTP‐bound active state and regulates circulation of vesicles between the Golgi and endosomal compartments. In present study, we investigated the roles of RAB14 during oocyte meiotic maturation. Materials and methods Microinjection with siRNA and exogenous mRNA for knock down and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
2
3
2
Order By: Relevance
“… 50 The more direct upstream regulators of LIMK1‐cofilin regulation are the Rho‐GTPases, whose activity promotes actin cytoskeletal remodeling and directs dendritic spine generation. 79 , 80 , 81 Our results are contrary to this. A limitation of our study is we did not detect changes in RhoA, an important molecule which directly regulates cofilin activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 50 The more direct upstream regulators of LIMK1‐cofilin regulation are the Rho‐GTPases, whose activity promotes actin cytoskeletal remodeling and directs dendritic spine generation. 79 , 80 , 81 Our results are contrary to this. A limitation of our study is we did not detect changes in RhoA, an important molecule which directly regulates cofilin activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has shown that activation of EphB2 downregulates cofilin activity through an active LIMK1 pathway 33,78 and activation of EphB1‐3 increases p‐cofilin levels in cell culture 50 . The more direct upstream regulators of LIMK1‐cofilin regulation are the Rho‐GTPases, whose activity promotes actin cytoskeletal remodeling and directs dendritic spine generation 79–81 . Our results are contrary to this.…”
Section: Discussioncontrasting
confidence: 98%
“…Previous results indicated that HT exposure interrupted ER distribution, and HS has been reported to increase incomplete migration of CGs in ovine oocytes (Gharibzadeh et al, 2015). RAB proteins function as vital regulators of intracellular vesicular transport, and act as transport vesicles on the actin and microtubule cytoskeleton (Zou et al, 2021). Studies also indicated that citrinin exposure caused defects in RAB11A (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Rho family small G proteins are involved in cytoskeleton rearrangement and cell division (Etienne-Manneville & Hall, 2002;Zhang et al, 2016). Mammalian studies revealed that RhoA and Rab14 regulate oocyte meiosis in early embryo development (Zhang et al, 2014;Zou et al, 2021). In addition, we discovered that the maturation and eggs production in female wasps were impaired when MmRho1 was knocked down (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…, 2014; Zou et al. , 2021). In addition, we discovered that the maturation and eggs production in female wasps were impaired when MmRho1 was knocked down (Fig.…”
Section: Discussionmentioning
confidence: 99%